1982
DOI: 10.1080/03079458208436079
|View full text |Cite
|
Sign up to set email alerts
|

Performance of meat‐type chickens test‐positive and ‐negative for lymphoid Leukosis virus infection1

Abstract: SUMMARYFour "sire-line" and seven "dam-line" breeding stocks of meat-type chickens were purchased as 1-day-old chicks from commercial breeders. One egg from each of 61 to 81 hens per stock was tested at 245-280 days of age for presence of group specific antigen of the lymphoid leukosis virus (LLV). Subsequently, cloacal swabs collected at 42 days of age from 93 male and 188 female progeny of particular "dam-line" stocks were tested for LLV. The percentage of LLV shedders in the individual stocks varied from 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Ignjatovic showed that hens which tested negative for gsa in egg albumen, transmitted replication competent endogenous ALV to embryos and this was possibly how infection was perpetuated in this study. Infections with exogenous ALV were detected in the original breeding stock from which sire and dam populations were synthesized (Gavora et al, 1982). It was thus surprising that the incidence of inection was very low in the populations developed.…”
Section: Discussionmentioning
confidence: 97%
“…Ignjatovic showed that hens which tested negative for gsa in egg albumen, transmitted replication competent endogenous ALV to embryos and this was possibly how infection was perpetuated in this study. Infections with exogenous ALV were detected in the original breeding stock from which sire and dam populations were synthesized (Gavora et al, 1982). It was thus surprising that the incidence of inection was very low in the populations developed.…”
Section: Discussionmentioning
confidence: 97%
“…ALV-infected hens that test positive for group-speci® c antigens (GSA) in egg albumen are called shedders. Eggs from GSA shedding hens are characteristically lower in quality, fertility, and hatchability than eggs from non-GSA shedding hens (Garwood et al, 1981;Gavora et al, 1980Gavora et al, , 1982.…”
Section: Introductionmentioning
confidence: 99%
“…These viruses cause serious economic losses in the poultry industry worldwide since infected chickens not only develop neoplasia, but also have decreased production ef® ciency (Gavora et al, ,1982Crittenden, 1991). ALV is categorized into subgroups A, B, C, D, E, and J according to their ability to infect chicken embryo ® broblasts (CEF), patterns of viral interference with other viral subgroups, and viral envelope antigens (Vogt & Ishizaki, 1966;Duff & Vogt, 1969;Hanafusa, 1975;Bova et al, 1986;.…”
Section: Introductionmentioning
confidence: 99%
“…Two developments in the 1970s led to widespread efforts by poultry breeding companies to eradicate ALVs. First was the development of rapid test procedures for detecting the infection in breeding stock (Spencer et al, 1976(Spencer et al, , 1977, and second was the discovery that subclinical infections with ALV substantially reduced egg production and also affected other production traits (Spencer et al, 1979;Gavora et al, 1982;Gavora, 1987). Programmes to eradicate ALV have been successful and egg-laying stocks of a number of primary breeders test negative for these viruses.…”
Section: Introductionmentioning
confidence: 99%